Tactile Perception of Textiles in a Virtual-Reality System - Allerkamp, Dennis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Virtual Reality (VR) has a lot of applications ranging from entertainment to mechanical design and medical training. VR systems are often used in training situations where training in a real environment would be inappropriate and possibly even dangerous. This work was part of the EU funded HAPTEX project, which aimed at developing a VR system for the visual and haptic presentation of textiles.
Human Perception -- Devices for Tactile Simulation -- Generation of Virtual Surfaces -- Tactile Rendering -- Summary and Outlook.
Keywords: Engineering; Textile industry; Artificial intelligence; Consciousness; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Textile Engineering; Cognitive Psychology